THE ROLE OF COUNSELING TEACHERS IN INCREASING STUDENTS 'LEARNING MOTIVATION AT THE STATE JUNIOR HIGH SCHOOL 3 TONDANO - Tabita Token (Prodi Bimbingan Konseling Universitas Negeri Manado, 2020)
This study aimed to determine the role of counseling guidance teachers in increasing student motivation at State Junior High School 3 Tondano. This type of research is qualitative research. The main research instrument in this study was the researcher himself. There were two sources of data in this study, the first one was primary data sources, namely counseling teachers, and secondary data sources, namely vice-principals and students. The triangulation method was used to assure the validity of the data. Data analysis was carried out in three stages, namely data reduction, data display, and conclusion drawing. The results revealed that the role of counseling guidance teachers in increasing student motivation at State Junior High School 3 Tondano was not optimal. This is influenced by three factors, such as; BK teachers do tasks outside their main duties, facilities are not adequate and human resources are not sufficient.